Analisis Semiotika Makna Komunikasi Keluarga Pada Film Ngeri-Ngeri Sedap - Rangga Arsati, Mayang Suci Dewi; Nurhadi, Zikri Fachrul; Suseno, Novie Susanti (Avant Garde, 2023)
The research was motivated by family conflicts which refer to divorce due to family communication that does not run smoothly illustrated in a study entitled Semiotic Analysis of the Meaning of Family Communication in the Film Ngeri-Ngeri Sedap. This study aims to explain signs, objects and interpretations about the meaning of family communication, with the hope that family relationships can be a place to lean without misunderstandings due to poor communication. The film, directed by Bene Dion Rajagukguk, tells the story of a family with children who are reluctant to return home from a foreign place which makes Pak Domu and Mak Domu pretend to be divorced so that the children can be reunited. This research is descriptive with a qualitative approach based on Charles Sanders Pierce's Semiotic Theory. Data collection techniques carried out by researchers are indirect observation, interviews and literature studies. This research was conducted on film then using indirect observation. Researchers will select several scenes that show the family's communication process. Then, researchers will analyze the meaning of family communication through signs, objects, and interpretations in the film Ngeri-Ngeri Sedap Researchers took 5 scenes to be observed based on the findings obtained by signs, interaction of Mr. Domu's family when solving problems, objects of a piece of image that shows things that trigger conflicts and also the communication process that is established in Mr. Domu's family, interpretant, the deep meaning of a film image of family reality that is displayed and felt by film connoisseurs.